Pengembangan LKS Pada Materi Perkalian Dan Pembagian Bilangan Bulat Menggunakan Pendekatan Realistik Berbasis Mangrove - Chairul Fajar Tafrilyanto; Bambang Kurnadi (Universitas Sarjanawiyata Tamansiswa, 2019)
Camplong Beach is one of the beaches on the island of Madura, along the road at the beach camplong overgrown with mangrove trees, adding to the beauty of the beach. Based on the beauty, the teacher has never used the natural beauty around to be associated with learning in order to increase students’ motivation in learning. The aim of this study was to develop Students’ Worksheets on multiplication and distribution of Round Numbers using valid and practical mangrove-based realistic. This research is a development research that refers to a simplified Thiagarajan 4-D model which becomes three stages including defining, designing, developing. The devices obtained are Student Worksheets and RPP. The results of the study showed the Student Worksheet on multiplication and distribution of integers using valid and practical mangrove-based realistic